Het blazoen ontsmet. Adellijke heraldiek als toe-eigening van eer en deugd, 1550-1750 - Duerloo, L. (BMGN - Low Countries Historical Review, 2008)
Purified Blazons: Noble Heraldry as the Appropriation of Honour and Virtue, 1550-1750Noblemen were the most important users of heraldry in the Middle Ages, yet they did not enjoy a monopoly on bearing coats of arms nor did they employ a distinct heraldic language. All of this changed towards the end of the sixteenth century. Taking its cue from heraldic treatises, the nobility appropriated exclusive heraldic rights by law. In the Habsburg Netherlands, they obtained the prerogative to use external ornaments around their shields. In other regions, the noble quest for distinction could lead to anything from a total ban on non-noble arms to restrictions on the display of certain external ornaments. The interplay between state formation and the relative share of the nobility in the total population seems to have determined the outcome of this process. At the same time, the symbolism of noble arms became distinct from that of other groups of armigers. The noble shield lost its direct – often canting – message and became a mirror of the privileged status of the bearer. Henceforth, it was not the personal achievements of the individual, but the honour and virtue of the noble estate that dictated heraldic compositions. This article is part of the special issue 'The history of the nobility in the Netherlands and Belgium'.